2004
DOI: 10.3354/dao058009
|View full text |Cite
|
Sign up to set email alerts
|

Ichthyobodo necator (Kinetoplastida)-a complex of sibling species

Abstract: Ichthyobodo necator is a parasitic flagellate that attacks fishes, causing disease problems in freshwater worldwide. Findings of similar flagellates in strictly marine fishes have indicated that ichthyobodiosis may be caused by more than 1 flagellate species. We obtained partial small subunit rDNA (ssu rDNA) sequences of 14 Ichthyobodo isolates originating from fishes in Norway, Japan, Singapore, South Africa and Brazil, and identified 8 strains or species, including 2 species infecting cultured salmon in Norw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(72 citation statements)
references
References 22 publications
2
69
1
Order By: Relevance
“…This study is the first attempt to gain a more complete picture of the types and numbers of pathogens that can be involved in the development of diseases in Norwegian production of salmonids with a main focus on PGI, PD, HSMI and CMS. These diseases were selected due to the large discrepancies between the observed pathology and mortality in marine already recognised that several pathogens are associated with gill diseases (A. Nylund et al 1998, 2009a,b, Kvellestad et al 2003, Draghi et al 2004, Fridell et al 2004, Todal et al 2004, Callahan et al 2005, Young et al 2007, Steinum et al 2008, and it has also proven difficult to perform challenge experiments with most of these agents. The other 3 diseases, PD, HSMI and CMS, are all associated with the presence of viruses , 2006, Vågenes et al 1999, Nylund 2001, Kongtorp et al 2004a, Bruno & Noguera 2009, Fritsvold et al 2009, Palacios et al 2010, but it is difficult, in challenge experiments, to reproduce both the mortality and all the pathological changes observed during outbreaks in farms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study is the first attempt to gain a more complete picture of the types and numbers of pathogens that can be involved in the development of diseases in Norwegian production of salmonids with a main focus on PGI, PD, HSMI and CMS. These diseases were selected due to the large discrepancies between the observed pathology and mortality in marine already recognised that several pathogens are associated with gill diseases (A. Nylund et al 1998, 2009a,b, Kvellestad et al 2003, Draghi et al 2004, Fridell et al 2004, Todal et al 2004, Callahan et al 2005, Young et al 2007, Steinum et al 2008, and it has also proven difficult to perform challenge experiments with most of these agents. The other 3 diseases, PD, HSMI and CMS, are all associated with the presence of viruses , 2006, Vågenes et al 1999, Nylund 2001, Kongtorp et al 2004a, Bruno & Noguera 2009, Fritsvold et al 2009, Palacios et al 2010, but it is difficult, in challenge experiments, to reproduce both the mortality and all the pathological changes observed during outbreaks in farms.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the agents that are associated with PGI are commonly found in all areas with salmon farming in Norway; among these are Parvicapsula pseudobranchicola, Ichthyobodo sp., Trichodina spp., SGP virus, and Chlamydia-like species (A. Nylund et al 1998, Todal et al 2004. Neoparamoeba perurans seem to be mainly distributed in western Norway (A.…”
Section: Proliferative Gill Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ichthyobodo is a genus of flagellate protozoan that is well documented as a serious pathogen of farmed fish worldwide (Woo 2006). A single species, Ichthyobodo necator, was originally considered to be responsible for all infections, until Todal et al (2004) showed that I. necator is in fact a complex of sibling species. Callahan et al (2005) identified a complex of 9 different species with low host specificity, one of which was capable of infecting both marine and freshwater fish.…”
Section: Protozoamentioning
confidence: 99%
“…The genus comprises only one valid species, I. necator (Henneguy, 1883) (see Lom & Dyková 1992). However, recent molecular studies have revealed that there are several species within the genus Ichthyobodo in both fresh-and seawater, and suggest that I. necator sensu Henneguy (1883) is a parasite infecting salmonids as well as sticklebacks in freshwater (Todal et al 2004).…”
Section: Introductionmentioning
confidence: 99%